Accounting for managers: A skill-buidling approach - Treesa, Jency (London Routledge, 2025)
This book presents fundamental aspects of financial accounting, its basic terminology, the accounting process and the preparation of a journal, ledger, trial balance, income statement and balance sheet. It also introduces complex topics like tools of management accounting, sustainability reporting and financial reporting. The volume comprehensively delivers lessons and examples to build strong accounting skills guiding readers to learn how to read and analyse financial statements, and discusses the theoretical concepts followed by elaborating on the accounting process in a simple and lucid style.